Рейтинговое управление инвестиционной привлекательностью Украины - Можаровская, П.П; Добряк, Ю.С. (Культура народов Причерноморья, 2013)
В статье рассмотрено современное состояние инвестиционной деятельности в Украине, проанализирована динамика поступления прямых иностранных инвестиций в экономику страны за последние годы. Исследованы позиции Украины в международных рейтингах конкурентоспособности экономики и инвестиционной привлекательности (индекс глобальной конкурентоспособности, индекс экономической свободы, индекс легкости ведения бизнеса Doing Business, индекс инвестиционной привлекательности Украины). Определены препятствия для развития инвестиционного климата и направления его улучшения. У статті розглянуто сучасний стан інвестиційної діяльності в Україні, проаналізовано динаміку надходження прямих іноземних інвестицій до економіки країни за останні роки. Досліджено позиції України за міжнародними рейтингами конкурентоспроможності економіки та інвестиційної привабливості (індекс глобальної конкурентоспроможності, індекс економічної свободи, індекс легкості ведення бізнесу Doing Business, індекс інвестиційної привабливості України). Визначено перешкоди для розвитку інвестиційного клімату та напрями його покращення. The purpose of this article is to determine the investment attractiveness of Ukraine by means of the main rating indicators of competitive advantages assessment of attracting foreign direct investments (FDI). The authors of the article investigate the present situation of attracting FDI in the Ukrainian economy over the last three years. The meaning of rating management concept and its influence on decision-making about capital investments in economy of any country is considered. The place of Ukraine among international organizations and institutes ratings such as the World Economic Forum, the group of the World Bank, the European Business Association is analyzed. The dynamics of indicators changes of Ukraine at the international ratings over the recent years is investigated. The article determines the weaknesses of Ukraine in terms of the Global Competitiveness Index (institutions, macroeconomic stability, goods market efficiency, financial market sophistication, business sophistication), the Index of Economic Freedom (business, trade, investment freedom), the Doing Business indicators (starting a business, registering property, paying taxes, enforcing contracts, insolvency), the Investment Attractiveness Index of Ukraine (tax burden, corruption, an unstable political situation). The article points out the need of comprehensive use of rating management of investment attractiveness which can identify and react to the weaknesses in the investment activity of Ukraine.